Financial Performance of The Tourism Industry in Indonesia and Asean Countries from the Stakeholder Perspektive - Subangkit, Andreas; suhardjanto, djoko (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2018)
Tourism industrial financial performance is important to be studied because the contribution of the tourism sector in Indonesia is still very small to GDP, earnings volatility in the tourism industry is strongly influenced by global economic conditions, especially foreign tourist visits from countries with slowing or crisis economic. This study will examine the influence of stakeholder responsibility on financial performance by using samples of the tourism industry in the ASEAN region. The stakeholders’ influence studied are the responsibility to shareholders, government, creditors, suppliers, employees and customers.The population in this study was the tourism companies in five ASEAN countries which are in the top five categories of tourism performance. The population of the study was 52 companies consisting of 13 companies from Singapore, four companies from Malaysia, eight companies from Thailand, four companies from Indonesia and 23 companies from Sri Lanka. The sampling method used purposive sampling while the data analysis method used multiple regression analysis.The results of the regression analysis show that the responsibilities to the creditors and customers have a significant effect on the company’s performance. Meanwhile, the responsibilities to the shareholders, government, employees, suppliers, and company size have no significant influence on the company’s financial performance.